Earnings Quality: The Effect of Investment Opportunity Set (IOS), Ownership Structure, and Book Tax Differences (E-Jurnal Akuntansi, 2026)
Not a few companies listed on the IDX carry out manipulation of financial reports by presenting false profits, so that the quality of profits is doubted by potential users of financial statements. This research aims to examine the influence of the Investment Opportunity Set (IOS), ownership structure, and book tax differences on earnings quality. The data used is manufacturing companies listed on the IDX for the 2017- 2021 period. The research sample was 57 companies with 200 observations found. The research analysis method is multiple linear regression which includes descriptive statistical methods, classical assumption testing, and hypothesis testing using SPSS as a data analysis tool. The results of the research conducted state that the Investment Opportunity Set (IOS) has a positive impact on earnings quality, while ownership structure and book tax differences do not have an impact on earnings quality.
Keywords: Investment Opportunity Set; Ownership Structure; Book Tax Differences; Earnings Quality